Climate change and the suitability of local and non‐local species for ecosystem restoration. (13th December 2021) - Harrison, Peter A.
Summary: Restoring damaged, degraded and destroyed forest ecosystems to a target state often follows a local‐is‐best approach. However, rapidly changing climates may result in the local species no longer being the best now or into the future. This raises questions about whether there is a need to consider emerging ecosystems that bring together local and non‐local species that have not historically co‐occurred to ensure climate‐resilience of restored forest ecosystems; or whether non‐regional species may be needed to support ecosystem functionality in some areas. In this study, I present an experimental framework to assist decision‐making by evaluating the suitability of local and non‐local native species for ecosystem restoration under current and predicted climates. I applied this framework using the Tasmanian Midlands, Australia, as a case study, focusing of the diverse eucalypt flora of the island. Three key findings emerged. Firstly, the climate of the Midlands has rapidly changed across this biodiversity hotspot over the last century, and current mean annual maximum temperatures are already tracking worse case climate change scenarios. Secondly, using a combination of climate envelope modelling and habitat suitability modelling, I identified the degree to which the Midlands region provides suitable climate habitat for a range of local and non‐local Eucalyptus species now and into the future. Thirdly, although the Midlands is predicted to support suitable climate habitat for 82% of the regionally local eucalypt species now and into the future, it is predicted that the local populations of these least vulnerable species may be at risk of climate maladaptation, particularly in the northern regions of the Midlands. Models suggests that mixing local seed with non‐local seed sources currently occupying habitat with a climate that is predicted for the Midlands will be required. The study provides a basis for managers to consider the suitability of regionally local species and identify potential areas where local seed may need to be supplemented with non‐local seed for ecosystem restoration in the face of climate change.